Pengaruh Internal Service Quality (INTQUAL) terhadap Kepuasan Karyawan di RS Islam Ahmad Yani Surabaya - Ismiyatul Izza; Budhi Setianto; Inge Dhamanti (Jurnal Manajemen Kesehatan Indonesia, 2021)
The job satisfaction that employees get at the organization depends on whether or not the employee's needs are met. Employee needs that can be met will provide job satisfaction. The greater the employee's needs that can be met, the higher the employee's job satisfaction. Meanwhile, if the employee's needs are not met, the employee will have dissatisfaction. Objective: To identify the influence of internal service quality (intqual) on employee satisfaction at RSIAS. Methods: This study analyses an employee satisfaction survey conducted in 2020 using a cross-sectional study design. Population of this research is all employees in RSIAS. The sample of this study is also all employees in RSIAS, which is 421 people. The satisfaction survey is filled in using a score of 1 to 5, then averaged so that a score is obtained to determine the category of each aspect. The data obtained were analyzed based on the theory of internal service quality and employee satisfaction, then tested using a multiple linear regression statistical test model to determine the effect of internal service quality (intqual) on employee satisfaction at RSIAS. Results: The results of statistical tests showed that the value of p = 0.000, meaning that internal service quality has an effect on employee job satisfaction because the value of p <0.05. Several aspects of internal service quality affect job satisfaction, namely the aspects of tools, policies and procedures, management support, goal alignment, effective training and reward and recognition.